2015
DOI: 10.19173/irrodl.v16i6.2153
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities and Threats of the MOOC Movement for Higher Education: The European Perspective

Abstract: The Massive Open Online Course (MOOC) movement is the latest "big thing" in Open and Distance Learning (ODL). MOOCs offer both opportunities and threats that are extensively discussed in the literature, including the potential of opening up education for all at a global scale. 21On the other hand, MOOCs challenge traditional pedagogy and raise important questions about the future of campus-based education. However, in discussing these opportunities and threats the majority of the literature tends to focus on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 17 publications
1
28
0
4
Order By: Relevance
“…Moreover, in Europe MOOCs seem to have revitalized online learning within HEIs (Teixeira, Volungeviciene, & Mazar, 2014). Schuwer et al (2015) studied how experienced open and distance learning (ODL) leaders from several European HEIs with considerable experience with MOOCs approached and judged opportunities and threats of MOOCs in HEIs. They found that most of these include accreditation (ECTS), innovation, and availability of multiple platforms .…”
Section: The Diversity Of Moocsmentioning
confidence: 99%
“…Moreover, in Europe MOOCs seem to have revitalized online learning within HEIs (Teixeira, Volungeviciene, & Mazar, 2014). Schuwer et al (2015) studied how experienced open and distance learning (ODL) leaders from several European HEIs with considerable experience with MOOCs approached and judged opportunities and threats of MOOCs in HEIs. They found that most of these include accreditation (ECTS), innovation, and availability of multiple platforms .…”
Section: The Diversity Of Moocsmentioning
confidence: 99%
“…Although this study is limited, the design criteria of the course, the pedagogical model on which this is supported, and the methods applied for this analysis provide other researchers and educators with clues for better understand the dynamic process of social learning in social MOOCs. to Schuwer et al (2015), the MOOC movement is the latest "big thing" in Open and Distance Learning (ODL) and threatens to significantly transform higher education.…”
Section: Introductionmentioning
confidence: 99%
“…Although this study is limited, the design criteria of the course, the pedagogical model on which this is supported, and the methods applied for this analysis provide other researchers and educators with clues for better understand the dynamic process of social learning in social MOOCs. to Schuwer et al (2015), the MOOC movement is the latest "big thing" in Open and Distance Learning (ODL) and threatens to significantly transform higher education.A simple definition, by OpenupEd (2015), says that MOOCs are "courses designed for large numbers of participants, that can be accessed by anyone anywhere as long as they have an internet connection, are also open to everyone without entry qualifications, and offer a full/complete course experience online for free" (p. 1). …”
mentioning
confidence: 99%
“…This is important for analyzing, for instance, whether a learner is likely to purchase a certificate based on their learning. This will be important is determining whether MOOCs can overcome the challenges posed of them [12] and transition from 'innovation platforms' [13] to mainstream educational provision. This vein of research will help in determining people discuss and recommend MOOCs such as on social media for example [14].…”
Section: Discussionmentioning
confidence: 99%